Combined effect of multiwalled carbon nanotubes, graphene nanoplatelets, and aluminum trihydride on the thermal stability of epoxy composites. Issue 3 (15th December 2021) - B. M., Madhu; Rashmi,; R. R. N., Sailaja; J, Sundara Rajan
Abstract: Glass fiber reinforced epoxy matrix is modified with a hybrid combination of fillers, and composites were fabricated using the advanced pultrusion technique. The focus of the investigation was to comprehensively understand the synergy between the carbon nanofillers and the role of aluminum trihydride on the thermal characteristics. A ratio of 2 wt% of multiwalled carbon nanotubes and 3 wt% of graphene is established by prior optimization technique for improved thermal properties. Using X‐ray diffraction analysis, the presence of the two carbon fillers was confirmed. Aluminum trihydrate was incorporated in the epoxy matrix with the objective of improving the thermal properties. By thermogravimetric analysis and differential scanning calorimetry, assessment of the thermal properties of the composites has been undertaken. The use of the two carbon fillers leads to enhancement of the thermal properties and contrary to expectations, the composites with hybrid fillers undergo minimal degradation due to pyrolysis. Uniform dispersion of the nanoparticles and good interfacial bonding of fillers with the epoxy are observed to be critical for the enhancement of thermal properties. The ratio of the two carbon fillers used helps in their preferential alignment and hence significant improvements in thermal properties are observed. Glass transition temperature reveals a 13°C increase increases due to the inclusion of carbon nanofillers and aluminum trihydride. Abstract : Composites with glass fiber reinforced epoxy matrix were made using pultrusion. The study's analyses effect of carbon nanofillers and aluminum trihydride on composites thermal characteristics. Morphology of composites is studied X‐ray diffraction and scanning electron microscope. Thermal characteristcs of composites were studied using thermogravimetry analysis and differential scanning calorimetry. Increasing thermal properties needs homogeneous nanoparticle dispersion and good filler‐epoxy interfacial bonding.